STUDI KUALITATIF TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN KEUANGAN USAHA MIKRO, KECIL DAN MENENGAH - Duryana, Duryana; Andanika, Andanika; Arfah, Dwi Astuty (Bisnis-Net, 2024)
This study aims to identify and analyze the factors that influence financial management in Small and Medium Enterprises (SMEs) through a qualitative approach. The focus of this research is to understand how internal and external factors play a role in financial decision-making as well as the management of cash flow, investment, and funding sources in the SME sector. Data were collected through in-depth interviews with owners and managers of SMEs in Makassar, which is one of the cities with significant SME development in Eastern Indonesia. in Eastern Indonesia. The results show that internal factors, such as such as financial literacy, personal financial management habits, organizational structure, and adoption of financial technology, have a major influence on the effectiveness of financial management. In addition, external factors, such as access to financing, macroeconomic conditions, market competition, and government policies also have a substantial impact on the stability of financial management. Government policies also have a substantial impact on the financial stability of SMEs. SMES Based on these findings, it is recommended that financial literacy literacy as well as policy support that facilitates access to financing and use of technology to strengthen SMEs' financial management. This research provides insights for policy makers and SME owners to create more effective and adaptive financial management strategies in a dynamic business environment.